What Catullus wrote : problems in textual criticism, editing and the manuscript tradition - Kiss, Dániel; Biondi, Giuseppe Gilberto; Butterfield, David; Gaisser, Julia Haig; Heyworth, S. J.; Ramírez de Verger, Antonio (Classical Press of Wales, 2015)
"The volume aims to set an example of a collaborative approach to textual criticism, in which significant choices are based not on the judgement of a single authoritative editor, but on the outcome of debate between scholars who represent a broad range of viewpoints"--Bookjacket